An Escherichia coli tyrosine transfer RNA is a leucine-specific transfer RNA in the yeast Saccharomyces cerevisiae. - Edwards, H (1991)
While the Escherichia coli Su-3 (tyrT) tyrosine tRNA suppressor inserts only tyrosine at amber codons in E. coli, we show here that in Saccharomyces cerevisiae this tRNA inserts leucine and no significant amounts of any other amino acid. Thus, the E. coli tyrosine tRNA is functionally a leucine tRNA in yeast cytoplasm. This functional identity may correlate with a structural relationship between the E. coli tyrosine and yeast leucine tRNAs, which are both members of the uncommon type II class of tRNA structures. The results raise the possibility that in evolution a tRNA may be more closely related to a tRNA of different acceptor specificity, but of the same type class, than to one with the same amino acid specificity, but of a different type class.